Analisis Produksi dan Pendapatan Usahatani Padi Sawah (Suatu Studi pada Penerapan Sistim Tabela Super dan Sistem Tapin di Kabupaten Bombana) - Rahmadani, Riska; Limi, Muhammad Aswar; Slamet, Agustono (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
This research aims to assess the labor use, production, and revenue of lowland rice farming using the Tabela Super and Tapin systems, as well as the differences in productivity and income between the two. This study took place from July to December 2021, and the research venue was chosen on purpose. The farmers of the Tabela super system and the farmers of the Tapin system were divided into two groups to determine responders (random cluster sampling). There were 122 lowland rice farmers, 111 super table farmers, and 11 Tapin farmers among the respondents. The Table Super system employed a simple random sample approach from that group, taking 10% of the total population of Tabela Super farmers, 11 respondents were paddy field farmers, and 11 respondents from the Tapin system used the census method. According to the findings, respondents' average production for rice farmers utilizing the Tabela Super System is 4,712 kg, while farmers using the Tapin system produce 3,300 kilograms. Rice farmers using the super table method earn an average of IDR10.177.656, while those using the Tapin system earn an average of IDR5.011.994. The t-test value shows that the difference in lowland rice farmers' production with the Tabela Super System and the Tapin system has a significance value of t of 0.040 < 0.05. The statistical test results of the t-test show that the difference in lowland rice farmers' income with the Tabela Super System and the Tapin system has a significance value of t of 0.000 < 0.05.